2014
DOI: 10.2224/sbp.2014.42.2.313
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index, Obesity, and Self-Control: A Comparison of Chronotypes

Abstract: The correlation between evening type, body mass index (BMI), and obesity has attracted the attention of researchers. In this study, I surveyed a sample of adults drawn from the general population in the US to examine whether or not evening types have a higher BMI than do other chronotypes and whether or not they are more likely than other chronotypes to become obese. I also proposed a personality-based explanation of the relationship between BMI, evening type, and obesity, with self-control as the mediator. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Also, a Spanish cohort study among 4243 adults with 3•5 years of follow-up indicated no relation between total energy intake in the evening and weight gain (53) . The majority of other studies investigating the relation between chronotype and anthropometric outcomes indicated that evening types had higher BMI and were more likely to gain weight than morning types (26,54) .…”
Section: Chronotypes and Anthropometric Measuresmentioning
confidence: 99%
“…Also, a Spanish cohort study among 4243 adults with 3•5 years of follow-up indicated no relation between total energy intake in the evening and weight gain (53) . The majority of other studies investigating the relation between chronotype and anthropometric outcomes indicated that evening types had higher BMI and were more likely to gain weight than morning types (26,54) .…”
Section: Chronotypes and Anthropometric Measuresmentioning
confidence: 99%
“…Defined as the capacity to inhibit immediate impulsive thoughts, emotions, and/or behaviors (de Ridder, Lensvelt-Mulders, Finkenauer, Stok, & Baumeister, 2012), self-control is implicated in an array of social and personal behaviors (Baumeister, Heatherton, & Tice, 1994;Tagney, Baumesiter, & Boone, 2004). For example, low levels of self-control are linked to increased substance abuse among college students (Ford & Blumenstein, 2013), impulsive purchasing (Baumeister, 2002), obesity (Lili, 2014), and increased affective symptomology, such as depression and anxiety (Tangney, Baumeister, & Boone, 2004). Conversely, high self-control brings with it a range of benefits including lower risk of psychopathology, better emotional adjustment to stress, decreased alcohol use, healthier relationships, and, among college students, higher grade point averages and lower school burnout (Seibert, May, Fitzgerald, & Fincham, 2016;Tangney et al, 2004).…”
Section: Posttraumatic Stress and Self-controlmentioning
confidence: 99%
“…It is associated with behaviors in various aspects, such as diet, interpersonal relationships, planning, and decision-making [ 20 ], and is reported as an important factor in facilitating desirable health behaviors [ 21 ]. In terms of obesity, self-control contributes to controlling BMI [ 22 ] and weight control behaviors [ 23 ]. While individuals with good self-control are able to steadily and appropriately manage their weight by ameliorating their lifestyle, those with poor self-control exhibit impaired impulse control and engage in undesirable eating behaviors [ 23 ].…”
Section: Introductionmentioning
confidence: 99%